Gender in Focus Identities, Codes, Stereotypes and Politics - Zamfira, Andreea; Montlibert, Christian de; Radu, Daniela (Verlag Barbara Budrich, 2018)
This book deals with the interplay between identities, codes, stereotypes and politics governing the various constructions and deconstructions of gender in several Western and non-Western societies (Germany, Italy, Serbia, Romania, Cameroon, Indonesia, Vietnam, and others). Readers are invited to discover the realm of gender studies and to reflect upon the transformative potentialities of globalisation and interculturality.